Estimasi Simpanan Karbon di Atas Permukaan Tanah pada Hutan Rakyat di Kawasan Perkotaan, Kota Bandar Lampung, Provinsi Lampung - Vita Arianasari; Hari Kaskoyo; Rahmat Safe'i; Arief Darmawan (Faculty of Forestry Universitas Gadjah Mada, 2021)
Community forest plays an equally important role in ecological aspects when compared to other types of forest, one of which is carbon storage that helps in mitigating global climate change. The existence of community forests that are part of urban areas is quite rare, so this research needs to be carried out considering its special location. This study aimed to estimate the carbon storage contained in urban community forests, Bandar Lampung City, Lampung Province. The methods used in this research were destructive and non-destructive. Carbon storage measurements were carried out in three carbon pools, namely aboveground biomass; necromasses; litter, and understorey. The measurements were carried out by a vegetation inventory on 15 plot clusters located in the study area. The results indicated that the average value of carbon storage was 54.59 tC/ha with a value interval of 48.93 tC/ha up to 60.26 tC/ha. Aboveground biomass held the largest percentage as a contributor to carbon storage 95.71%, followed by necromass 4.23%, litter and understory 0.05%.